The current status of biological treatment for uveitis. (2nd August 2020) - Gaggiano, Carla; Sota, Jurgen; Gentileschi, Stefano; Caggiano, Valeria; Grosso, Salvatore; Tosi, Gian Marco; Frediani, Bruno; Cantarini, Luca; Fabiani, Claudia
ABSTRACT: Introduction: Noninfectious uveitis represents one of the leading causes of blindness in developed Countries, compromising patients' quality of life and social functioning. The main treatment goals are the control of ocular inflammation, to avert and treat sight-threatening complications, thus preserving and/or restoring visual function. Areas covered: This manuscript deals with systemic therapy with biologic drugs for noninfectious uveitis. An extensive literature search in the MEDLINE database (via PubMed) has been performed up to June 2020. The major classes of biologic molecules employed in ocular inflammatory diseases have been reviewed, focusing on TNF inhibitors, IL-1, IL-6, IL-17, IL-23 inhibitors, interferons, rituximab, and abatacept efficacy and safety. An overview of most recent developments in the field has been provided as well, with reference to the experience with JAK inhibitors and with biosimilar drugs. Expert opinion: The development of the concept of targeted therapy and the subsequent introduction of biologic molecules in clinical practice have revolutionized the prognosis of uveitis. The target of a rapid and sustained steroid-free remission of ocular inflammation should be pursued for all patients early in the disease course, in order to have a better chance to improve the final visual outcome.